Effects of knock intensity measurement technique and fuel chemical composition on the research octane number (RON) of FACE gasolines: Part 1 – Lambda and knock characterization. (15th November 2021) - Hoth, Alexander; Kolodziej, Christopher P.
Highlights: The CFR knockmeter system filters out high frequency pressure oscillations. Paraffinic gasolines had higher knocking pressure oscillations for similar RON. Stoichiometric pressure transducer-based RON ratings correlated with standard RON. RON test and cylinder pressure transducer knock metric gives K = −0.5 in Octane Index. Abstract: The Research and Motor Octane Number (RON and MON) rate the knock propensity of gasoline in the Cooperative Fuel Research (CFR) engine by comparing the knock intensity of sample fuels relative to that of primary reference fuels (PRF), a binary blend of iso-octane and n-heptane. Important differences exist between standard octane testing and automotive spark ignition (SI) engine knock testing including speed, load, air-to-fuel equivalence ratio (lambda), and knock characterization, which lead to a discrepancy between a fuel's RON rating and its knock resistance characterized on an automotive SI engine based on knock-limited spark advance. This is the first of a set of three publications which modify operating parameters of the RON test method (ASTM D2699) to investigate the effects of these differences with automotive SI engine knock-limited spark advance testing. A fuel's standard RON is evaluated at the lambda of the highest knock intensity, whereas automotive SI engines typically operate at stoichiometry. This study analyzes the effects of a stoichiometric RON rating methodology. Additionally, the knock intensity response from the standard CFR knockmeter system is compared to a cylinder pressure oscillation-based knock intensity at several lambda settings. All experiments were performed with a set of seven Coordinating Research Council (CRC) Fuels for Advanced Combustion Engines (FACE) gasolines with approximately 95 RON. The fuel chemical composition impacted the lambda of the highest knock intensity, which resulted in fuel-specific offsets between the standard and stoichiometric RON ratings. The knock system comparison showed significant offsets between cylinder pressure-based and knockmeter-based knock intensity levels.